PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 008SUNGAI SEGAJAH KECAMATAN KUBU KABUPATEN ROKAN HILIR - Mawarni, Mawarni; Daud, Damanhuri; Munjiatun, Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to improve the learning process and achievement of school year 2014/2015. Studies students learning outcomes with average grade 57,75. While the value of minimum criteria of completeress is 65. This research is clasroom action research (CAR). Which is to inprove the secience studies achierment of fourth brade elementary school 008 Sungai Segajah Kubu Rokan Hilir District. The formulation of the problem is: Does the application of Inkuri guide can inperave the science studies studen learning outcomes elementary school 008 Sungai Segajah Kubu Rokan Hilir Distric. The incriasing of students achievmert happenet before CAR and there is in cereasing after first cycle about 57,75% in low categori, whereas after CAR on cycle 1 about 65,75% in medium and on cycle 2 about 69,75. In high categori. So that, there is increatif grade of science studies from based score to first cycle is about 13,84% and from based score to secord cycle is about 20,77%. The activity of the teacher is an averase grade on irst cycle about 62,5% in medium categori and the secord cycle is about 83,33% in high category. The activity of the students in second meeting on first cycle is average about 58,33% and the secord cycle is about 79,16%. The result of this research is the application of guiding Inkuiri can increase the secience studies students learning outcomes at fourth brade of elementary school 008 Sungai Segajah Kubu in Rokan Hilir District.Key word : Guiding Inkuiri, The science,s students achievement